Risk Management Practices Among Campus-Based MSMEs: A Qualitative Study at FEB Khairun University - Septy Indra Santoso; Meliana Meliana; Rinto Syahdan; Gisela S. Debeturu; Salwa Shobiha Buamona; Widyawati Muhlis; Chantika Alya Ruumbia; Sarmina Ali; Fitri Fahrudin; Jul Arvaji; Livi Meiga Putri (Journal of Marketing Management and Innovative Business Review, 2025)
This study aims to explore the implementation of business risk management among Micro, Small, and Medium Enterprises (MSMEs) operating within the campus environment of Khairun University, particularly at the Faculty of Economics and Business in Ternate City. Although numerous studies have discussed risk management in MSMEs, most focus on large-scale businesses or urban commercial settings. Only a few have examined campus-based MSMEs, which operate under distinctive institutional and market constraints. This research fills that gap by investigating how MSME actors in a university setting identify, analyze, and respond to business risks. A descriptive qualitative approach was employed, using in-depth interviews and participatory observation as data collection techniques. The unit of analysis in this study consists of three culinary MSME owners operating within the canteen area of the Faculty of Economics and Business, Khairun University. The informants were selected purposively based on their active involvement in daily business management and risk-handling practices. The findings reveal that effective risk management contributes positively to business sustainability, particularly in strategic decision-making and financial control. The scientific contribution (novelty) of this study lies in its focus on campus-based MSMEs, a context rarely explored in previous risk management literature. The study expands theoretical understanding of how the campus business environment—with its limited market scope and dependence on academic communities—shapes MSME risk management behavior. Furthermore, it provides a conceptual foundation for developing adaptive training and mentoring models to strengthen risk preparedness among MSMEs operating in higher education environments.